2008
DOI: 10.1007/s10646-008-0201-5
|View full text |Cite
|
Sign up to set email alerts
|

Variation of δ13C in Aegiceras corniculatum seedling induced by cadmium application

Abstract: To test whether the values of delta13C in mangrove plants are affected by Cd application, the seedlings of Aegiceras corniculatum, a dominant mangrove species, were cultured in soil supplied with CdCl2 solution at the concentration of 0, 0.5, 2.5, 5, 20, 30 and 50 CdCl2 mg/kg wet soils. Plants were grown in 10 replicate pots with 5 propagules each. After 5 months of Cd exposure, three pots contained 15 seedlings with average shoot heights were selected for each treatment. Leaves and roots of seedling were samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Similar to these studies' outcomes are those of Tam et al, (1997), Sur et al, (2006) and Wei et al, (2008). In addition, other likely implication of this observation is that the root might be acting as a barrier for heavy metal translocation thereby protecting the sensitive parts of the plant (e.g.…”
Section: Resultssupporting
confidence: 81%
“…Similar to these studies' outcomes are those of Tam et al, (1997), Sur et al, (2006) and Wei et al, (2008). In addition, other likely implication of this observation is that the root might be acting as a barrier for heavy metal translocation thereby protecting the sensitive parts of the plant (e.g.…”
Section: Resultssupporting
confidence: 81%
“…Metal accumulation in the roots has also been found by other authors (Wei et al, 2008;Gupta and Chakrabarti, 2013). Greater arsenic retention in the roots is one of the defense mechanisms of plants (Meharg and Macnair, 1991).…”
Section: Discussionsupporting
confidence: 78%
“…However, the changes in d 13 C were too subtle, in our opinion, to be the only cause of the notable reduction in growth detected. Wei et al (2008) observed that d 13 C was slightly affected by Cd exposure in mangrove (Aegiceras corniculatum (L.) Blanco) and roots were more sensitive than leaves. These authors observed that d 13 C also differed between plant parts, with assimilating organs showing lower values than non-assimilating or storage organs.…”
Section: Discussionmentioning
confidence: 98%